The Vitamin D Receptor as a Potential Target for the Treatment of Age-Related Neurodegenerative Diseases Such as Alzheimer’s and Parkinson’s Diseases: A Narrative Review - Władysław Lasoń; Danuta Jantas; Monika Leśkiewicz; Magdalena Regulska; Agnieszka Basta-Kaim (Cells, 2023)
The vitamin D receptor (VDR) belongs to the nuclear receptor superfamily of transcription factors. The VDR is expressed in diverse brain regions and has been implicated in the neuroprotective, antiaging, prosurvival, and anti-inflammatory action of vitamin D. Accordingly, a relationship between vitamin D insufficiency and susceptibility to neurodegenerative diseases has been suggested. However, due to the multitargeted mechanisms of vitamin D and its often overlapping genomic and nongenomic effects, the role of the VDR in brain pathologies remains obscure. In this narrative review, we present progress in deciphering the molecular mechanism of nuclear VDR-mediated vitamin D effects on prosurvival and anti-inflammatory signaling pathway activity within the central nervous system. In line with the concept of the neurovascular unit in pathomechanisms of neurodegenerative diseases, a discussion of the role of the VDR in regulating the immune and vascular brain systems is also included. Next, we discuss the results of preclinical and clinical studies evaluating the significance of vitamin D status and the efficacy of vitamin D supplementation in the treatment of Parkinson’s and Alzheimer’s diseases, emphasizing the possible role of the VDR in these phenomena. Finally, the associations of some VDR polymorphisms with higher risks and severity of these neurodegenerative disorders are briefly summarized.